2019
DOI: 10.1108/jarhe-12-2018-0254
|View full text |Cite
|
Sign up to set email alerts
|

Dual perspectives on learning analytics in higher education

Abstract: Purpose In higher education, the authors serve multiple stakeholders with varying perspectives on the institution’s learning analytic system. The purpose of this paper is to highlight dual perspectives within the learning analytics (LA) system in one institution: that of an administrator responsible for college-wide improvement, and a faculty member responsible for programmatic improvement. Design/methodology/approach This manuscript provides a critical perspective with dual sets of experiences and viewpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Despite the widespread use of LA in developed countries, a deep understanding of its usage in developing countries, the beneficiaries involved in its adoption and implementation and resulting perceptions have received negligible attention (Hommel et al, 2019;Parrish and Richman, 2019). El Alfy et al (2019) pointed out that there is no adequate research in specific regions such as North Africa and the Gulf area, which was confirmed by the literature review conducted in this study.…”
Section: Limitations and Future Research Directionssupporting
confidence: 51%
See 1 more Smart Citation
“…Despite the widespread use of LA in developed countries, a deep understanding of its usage in developing countries, the beneficiaries involved in its adoption and implementation and resulting perceptions have received negligible attention (Hommel et al, 2019;Parrish and Richman, 2019). El Alfy et al (2019) pointed out that there is no adequate research in specific regions such as North Africa and the Gulf area, which was confirmed by the literature review conducted in this study.…”
Section: Limitations and Future Research Directionssupporting
confidence: 51%
“…HEIs always seek new technology to help improve the quality of their operations, in order to cope with the growing competition at providing the labour market with qualified candidates that can fill in its gap. LA has been used by HEIs as it can help in the transformation of their culture to enable evidence-based decision-making (Parrish and Richman, 2019). Despite its realised role, the wide adoption of LA in HEIs is not sustained.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to properly train end‐users (at all levels) in the use of LA tools and data interpretation (see, for instance, Fearn & Koya, 2021; Herodotou et al, 2021). Parrish and Richman (2019) stated that within multiple stakeholder groups, there are individuals who may require training, time and continuous support to use LA in a meaningful way. For this reason, they advocate individualized and intensive professional development for the various stakeholders as part of the introduction of any new technology.…”
Section: Results and Findingsmentioning
confidence: 99%
“…It is necessary to properly train end-users (at all levels) in the use of LA tools and data interpretation (see, for instance,Fearn & Koya, 2021;Herodotou et al, 2021) Parrish and Richman (2019). stated that within multiple stakeholder groups, there are individuals who may require training, time and continuous support to use LA in a meaningful way.…”
mentioning
confidence: 99%
“…Some of the research has uncovered emerging privacy concerns. A reoccurring issue present in a number of studies is the perception that learning analytics presents a "big brother" type environment [41]- [46]. However, this literature set did not fully develop what faculty mean when they claim that analytics were "big brother-ish."…”
Section: Faculty Perspectives and Problemsmentioning
confidence: 99%